PROCUREMENT OF FERROTITIAN FROM METAL INDUSTRY WASTE BY METHOD OF ALUMOTHERMAL SYNTHESIS - A. A. Zhukova; K. B. Podbolotov; A. A. Izyumov; V. V. Petrenko (Литьë и металлургия)
Researches of procurement of ferrotitanium of Fti25 brand from waste products by method of aluminothermic synthesis are conducted. The thermodynamic analysis revealed that differences in using oxide of iron (Fe2O3) and iron cinder (Fe3O4) are subtle and it is confirmed by the experimental results. According to an elemental analysis, when using an iron cinder, the received alloy contains 18, 0–21,5 titanium and 68–73% of iron. Research of structure showed that at a crystallization of the received alloy two main phases are formed: exuberant, which is presented by dendrites with pronounced borders length of an axis of first order of a dendrite was about 250 microns and having the eutectic structure, is allocated in interdendritic space. It is established that the increase in a mass fraction of oxide of calcium in fusion mixture there is an increase in dispersion of structural components and some sferoidization, transition of an excess phase to globular.